Dengue in hospitalized children with sickle cell disease: A retrospective cohort study in the French departments of America. Issue 2 (February 2020) - Elenga, Narcisse; Celicourt, Donald; Muanza, Blandine; Elana, Gisèle; Hocquelet, Sévérine; Tarer, Vanessa; Maillard, Frédéric; Sibille, Gérard; Divialle Doumdo, Lydia; Petras, Marie; Tressières, Benoit; Etienne-Julan, Maryse
Abstract: Background: To describe the characteristics of dengue in sickle cell children and try to identify risk factors of severity. Methods: In this retrospective study, we describe the evolution according to genotype (SS or SC and controls) and severity. Results and conclusions: From 2005 to 2013, 106 hospitalizations for dengue fever were recorded, 35 SS genotype, 35 SC and 36 without SCD or any other chronic disease. The clinical evolution was quite different. During hospitalization, SC patients were more likely to develop multiorgan failure (31.4% versus 25.7% for SS, and 0% for controls, p = 0.001), or acute pulmonary complications than patients without SC sickle cell disease (14.3% versus 8.6% for SS, and 0% for controls, p = 0.03). Level 3 analgesic treatment was more frequent in SC patients (22.9% versus 3% for SS, and 0% for controls, p < 0.001). Patients with SC sickle cell disease had a higher proportion of severe forms of dengue (57.1% versus 37.1% for SS, and 0% for controls, p < 0.001) than patients without SC sickle cell disease. Transfer in intensive care unit was required for most SC patients (22.9% versus 3% for SS, and 0% for controls, p = 0.005).Fatal episodes were more frequent in SC patients than in patients without SC sickle cell disease (5 deaths versus 1 for SS and 0 for controls, p = 0.02). Thirty-three patients (47.1%) were diagnosed as having severe dengue (13 SS and 20 SC). On univariate analysis, age >10 years, acute pulmonary complications, multiorgan failure, severe anemia requiring transfusion, use of antibiotic treatment, need for treatment with morphine, and longer hospital stay were statistically more frequent in severe dengue-associated cases. Multiple logistic regression analysis showed that HbSC genotype and acute pulmonary complications, were significantly associated with severe dengue. In the multivariate model, the area of the ROC curve was 0.831. Children with SC genotype, typically thought to have less severe disease, actually had a higher rate of severe dengue and death than those with SS genotype.